Indemnity Clause in the Judicial System of Iran - Mohabbat Bayazid Nejad , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Indemnity clause enjoys special position in industrial contracts considering its importance and application. According to the studies, this structure has been originated from the tradition among businessmen which has been identified in the laws of England and other judicial systems throughout the time. Identifying the type of pre-contractual commitments and considering responsibility for the violator party have so many effects; such as: punishing the violator and preventing denying aggrieved party’s rights have been compensated in good will, helping judicial and juridical referents recognize how to punish the pre-contractual violators, filling legal gaps in the mentioned problem which prevents the abuse and exploitation of some people who are aware of such gaps in private contracts concluded with those with good will, expanding law theoretical knowledge about the mentioned problem and finally evolving and promoting the level of internal law and matching it with today’s problems of contracts laws. The current study aimed at investigating indemnity clause in the judicial system of Iran using analytical-descriptive method that the results demonstrate that the process of compensation highly determines the destination of the final contract, especially when there is signature of agreements in many cases which is not definitely devoid of judicial effect and may cause losing important concessions for each of contract parties.